(untitled) (The Arab Journal of Administration, 2026)
In the era of global networking, the development of social media allows the facilitation of electronic word-of-mouth (EWOM) on global and widely accessible platforms. People use such platforms to discuss and share feedback, reviews, or evaluations on products and services with their acquaintances, family, friends, or the public. This study examines the impact of EWOM characteristics (namely, quality/usefulness, quantity/intensity, valence, and recency) on EWOM credibility and social media customers’ purchase intentions, considering the mediation role of EWOM credibility. Study data were collected from 664 customers and analyzed by structural equation modeling. The findings revealed that EWOM characteristics and credibility have significant effects on purchase intention. EWOM quality/usefulness, quantity/intensity, and recency have significant effects on EWOM credibility. Furthermore, EWOM credibility mediates the effects of EWOM quality/usefulness and recency on purchase intention. This study provides empirical evidence that may help researchers and practitioners explore methods to encourage social media customers’ purchase intentions.